2020
DOI: 10.1111/ctr.14109
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes for infiltrative and restrictive cardiomyopathies under the new heart transplant allocation system

Abstract: Heart transplant (HT) allocation for patients with infiltrative, hypertrophic, and restrictive cardiomyopathies has been debated extensively, particularly during the development of the recent Organ Procurement and Transplant Network (OPTN) heart allocation policy. 1 Historically, under the three-tier system (Status 1A, 1B and Status 2) which came into effect on January 19th, 1999, patients were allocated based on the level of support they required. 2 Status 1A necessitated intensive care unit level support wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Thus, the smaller sample size and the different study design could potentially underpower statistical analyses of interest. 12,13 In conclusion, this analysis of the UNOS Registry showed that short-term and long-term all-cause mortality and rejection risks after isolated HT were not inferior in sarcoid cardiomyopathy as compared with other common types of non-ischaemic cardiomyopathy. These data suggest that HT can be safe and effective in this growing patient population with advanced HF due to CS.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the smaller sample size and the different study design could potentially underpower statistical analyses of interest. 12,13 In conclusion, this analysis of the UNOS Registry showed that short-term and long-term all-cause mortality and rejection risks after isolated HT were not inferior in sarcoid cardiomyopathy as compared with other common types of non-ischaemic cardiomyopathy. These data suggest that HT can be safe and effective in this growing patient population with advanced HF due to CS.…”
Section: Discussionmentioning
confidence: 67%
“…Patient characteristics at the time of listing were comparable between France and the United States, with more frequent use of balloon pump and inotropic support in the United States as the main exception. 25,26 In the new US system, the proportion of patients undergoing HT with status 1 to 3 is high (70.6%–76.3%), with nearly half of these patients having exception status. 25,26 Restrictive heart disease has been identified as a risk factor for posttransplant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In the new US system, the proportion of patients undergoing HT with status 1 to 3 is high (70.6%–76.3%), with nearly half of these patients having exception status. 25,26 Restrictive heart disease has been identified as a risk factor for posttransplant mortality. Recently, the 39th annual International Society for Heart and Lung Transplantation adult HT report, which focused on transplantation for heart disease with restrictive physiology, studied the effect of the restrictive disease type on posttransplant survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, US candidates with HCM and RCM had shorter waitlist time and lower waitlist mortality/delisting, although utilization of temporary MCS and ischemic time increased. 13,14 It is not surprising that RCM experienced higher mortality after transplant in the United States and France, given its frequent association with systemic diseases such as amyloidosis or sarcoidosis or prior radiation exposure. 15 The current analysis does not shed additional light on this finding.…”
Section: See Article By Legeai Et Almentioning
confidence: 99%